Intramedullary Nailing for Paediatric Diaphyseal Forearm Bone Fracture - Parajuli, N P; Shrestha, D; Dhoju, D; Dhakal, G R; Shrestha, R; Sharma, V (Kathmandu University Medical Journal, 2012)
Background Though most of the pediatric diaphyseal forearm bone fracture can be treated with closed reduction and cast application, indications for operative intervention in pediatric both-bone forearm fractures include open fractures, irreducible fractures, and unstable fractures. Controversy exists as to what amount of angulation, displacement, and rotation constitutes an acceptable reduction. Objective To review union time and functional outcome of pediatric diaphyseal forearm bone fracture managed with intramedullary rush pin by closed or open reduction. Methods Fifty patients with both bone fracture of forearm were treated with intramedullary rush pin by closed or open reduction were included in the study and followed up for minimum six months for radilological and functional outcome. Results Out of 50 patients, 31 underwent closed reduction and 19 underwent open reduction. All fractures maintained good alignment post operatively. Forty seven patients had excellent results with normal elbow range of motion and normal forearm rotation and three patients had good results. In all patients good radiological union was seen in three months time. Eight patients had minor complications including skin irritation over prominent hardware, backing out of ulnar pin, superficial skin break down with exposed hardware. Twenty-three (46%) patients had undergone implant removal at an average of 6 months (range 4-8 months) under regional or general anesthesia Conclusion Fixation with intramedullary rush pin for forearm fracture is an effective, simple, cheap, and convenient way for treatment in pediatric age group. DOI: http://dx.doi.org/10.3126/kumj.v9i3.6305 Kathmandu Univ Med J 2011;9(3):198-202